TH1.1: Can I speak to the manager? Unpacking intrahousehold decision-making in maize production in Kenya - Voss, Rachel C.; Gitonga, Zachary; Donovan, Jason A.; Garcia Medina, Mariana; Muindi, Pauline (International Maize and Wheat Improvement Center, 2022)
Research looking at the gender gap in uptake of agricultural technologies often assumes that men and women make farm management decisions as individuals. In fact, relatively little is understood about the dynamics of agricultural decision-making for plot management within dual-adult households. This study used vignettes to examine decision-making structures related to maize production in over 600 spousal-couple households in Kenya. The results indicate a high degree of joint management of maize plots (55%), although some management decisions—notably those related to purchased inputs—are more often controlled by men, while other decisions—including those related to hiring of labor and deciding how harvested maize will be used—are disproportionately controlled by women. The high prevalence of joint decision-making underscores the importance of ensuring that both men's and women's priorities, needs, and constraints are reflected in design and marketing of interventions to support maize production, including those related to breeding, seed systems, capacity building, and agricultural extension. Furthermore, evidence that men disproportionately control the decisions that most directly impact maize production potential, and that the rationales behind decision-making structures differ according to respondent gender, point to the relevance of gender-transformative approaches that increase respect for women's knowledge and build their influence over decisions that impact production potential directly.